The Relationship Between Internal Locus of Control And Cyberloafing Behavior Among Students At Universitas Negeri Padang - Amanda Martina Fauziah; Farah Aulia (International Journal of Health and Pharmaceutical (IJHP), 2026)
This study aims to examine the relationship between internal locus of control and cyberloafing behavior among students at Universitas Negeri Padang. A quantitative approach with a correlational research design was employed, involving 202 respondents selected via quota sampling. Due to non-normal and non-linear data distribution, the Spearman’s rho non-parametric statistical test was used for analysis. The findings revealed a significant positive relationship between internal locus of control and cyberloafing behavior, indicating that higher levels of internal locus of control are associated with increased cyberloafing activities. These results imply that students with a strong internal locus of control feel confident in managing their academic outcomes despite consciously engaging in non-academic online activities during lectures.